"Bring me sunshine, bring me (physical) strength": The case of dementia. Designing and implementing a virtual reality system for physical training during the COVID-19 pandemic. Issue 165 (September 2022) - Matsangidou, Maria; Frangoudes, Fotos; Hadjiaros, Marios; Schiza, Eirini; Neokleous, Kleanthis C.; Papayianni, Ersi; Avraamides, Marios; Pattichis, Constantinos S.
Highlights: Non-pharmacological interventions for people with dementia are of great importance. VR is a useful for boosting the training of people with dementia during Covid19. Fully-Immersive VR can improve the physical training of people with dementia. VR is feasible solution for people with dementia who reside in restricted hospital. Abstract: People living with Dementia (PwD) are amongst the most vulnerable populations in society, often depending on caregivers for their quality of life (QoL). Emerging research confirms the need for technological solutions to support non-pharmacological interventions that can enhance the QoL of PwD. This paper posits that Virtual Reality (VR) is a useful technology for boosting the physical training of PwD. In a study with PwD, we compared the conventional physical training PwD receive at a nursing home, against Semi Immersive VR (SIVR) and Fully Immersive VR (FIVR) training paradigms. We recorded the emotional behaviour, task-specific metrics, and level of independence of PwD during the training. The presence and usability of the systefm by both medical staff and PwD was also assessed. Results indicated that FIVR can improve the training of PwD leading to more accurate execution of the exercises while preventing external distractions. Beyond the findings, this article discusses the opportunities, challenges, along with the feasibility and acceptability of VR, to facilitate physical training for PwD who reside in restricted health care environments.